Edukasi Pijat Common Cold pada Ibu dan Kader sebagai Upaya Mengatasi Gejala Batuk Pilek pada Balita - Putri Aziizah Thurfah; Etika Dewi Cahyaningrum; Siti Haniyah (Yayasan Inspirasi El Burhani, 2026)
Introduction: Cough and cold are common health problems in toddlers that may cause sleep disturbances, decreased appetite, and risk of complications if not properly managed. One non-pharmacological approach that can be applied is common cold massage to help relieve respiratory symptoms. Objective: The purpose of this service was to improve mothers’ knowledge and skills in performing common cold massage to manage cough and cold symptoms in toddlers. Method: This public service was conducted at Posyandu Bunda Lestari 2 involving 50 mothers of toddlers. Education was delivered through lectures, discussions, demonstrations, and direct practice. Evaluation was carried out using pre-test and post-test questionnaires to measure knowledge improvement. Result: Before the intervention, 18% of mothers were in the good knowledge category, 38% moderate, and 44% poor. After education, 100% of participants were categorized as having good knowledge. Mothers were also able to correctly demonstrate the massage technique according to the guidelines provided. Conclusion: Education on common cold massage effectively improves mothers’ knowledge and skills in managing cough and cold symptoms in toddlers and can be applied as a simple, safe, and affordable home-based intervention.